Information institution review: Perpustakaan Wakaf MAIS / Azmi Ab Rahman and Mohd Nizam Yunus - Ab Rahman, Azmi; Yunus, Mohd Nizam (Faculty of Information Management, 2014)
Perpustakaan Wakaf is a special library situated at Wisma MAIS, Seksyen 3, Shah Alam, Selangor. Managed by our alumni, this special library is being supported by another three staff. The best thing about Perpustakaan Wakaf is that it is among the special library opens its door not only to their own staff but also to the public. Not only muslim patronize the library but non-muslims are also welcomed. In fact according to Perpustakaan Wakafs manager, Mr. Mohd Hafiz Bin Abdul Salam, the concept of Islam for all is being adapted by the library where their patrons are not only muslims but non-muslims as well. There are also non-muslims who registered themselves as library official member.